Medico Legal Aspects of Digital Health - Shaharuddin, Fadzlinda (International Journal of Human and Health Sciences (IJHHS), 2019)
The fast growth of digital technologies is currently transforming healthcare services provided worldwide. The technologies can be from digital communication technology to artific ia l intelligence devices. Therefore, current system and practice are encouraged to keep updated with the current trend. In order to ensure safety for both healthcare personnel and patient, Ministry of Health together with other relevant agencies are implementing changes in the current regulation to promote the development of new technology, to embrace in digital healthcare development and transform the current healthcare system from the complexity - to one of high impact, reasonable cost with great outcomes. Guidelines have been prepared and amended to ensure the new invention is safe for patient and compliant with current acceptable health care standard. However, with the development of new technology the doctors are vulnerable to new complaint and litigation as public nowadays more aware of their rights. And the best way to avoid medico legal issues, is by preventing them. International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 22